Not in employment, education or training: Mental health, substance use, and disengagement in a multi-sectoral sample of service-seeking Canadian youth. (April 2017) - Henderson, Joanna L.; Hawke, Lisa D.; Chaim, Gloria; ,
Abstract: Background: Youth who are not engaged in employment, education or training (NEET) face multiple health, economic and psychosocial challenges. Despite the popularity of the NEET metric internationally, there is a paucity of research describing Canadian NEET youth. Method: The proportion of NEET youth aged 12 to 24 presenting for services across multiple service sectors in Canada was examined. Their sociodemographic characteristics and mental health concerns were compared with those of their non-NEET peers. Results: Over a quarter of youth were NEET, and they presented for services across all sectors. NEET youth showed multiple psychosocial risk factors. They were also more likely to endorse substance use and crime/violence concerns than their non-NEET service-seeking counterparts. Gender-based differences were observed. Discussion: Since many youth presenting for services across sectors are NEET, youth-serving agencies should be prepared to offer a wide range of services to address their diverse needs. Implications for systematic screening and integrated service provision are discussed. Highlights: Describes Canadian youth not engaged in employment, education or training (NEET) In a multi-sectoral sample of service-seeking youth, over a quarter were NEET. NEET youth showed many risk factors, including substance use and crime/violence. Gender-based differences were also observed. Systematic screening and integrated services are needed for these high risk youth.